Body-Crossroads as Performing Experience in the Congado Ritual - Ramos (Universidade Federal de Uberlândia, Brazil), Jarbas Siqueira (Revista Brasileira de Estudos da Presença, 2022)
This article discusses the congado ritual as a performing experience based on the notions of body-crossroads. First, it studies the congado universe and its symbolic complexity, perceiving it as a crossroad culture. The congado ritual is the nodal point of this manifestation. The relation between the body and the performance characterizes the ritual. This work is based on theoretical studies and field research carried out with the Catopês of the city of Bocaiúva, in the state of Minas Gerais, Brazil, and aims to be a reference for studies on Brazilian culture, especially on Afro-Brazilian cultural manifestations.